Informational support for women with endometriosis: a scoping review - Deniz Senyel; James H. Boyd; Melissa Graham (BMC Women's Health)
Abstract Background Ten per cent of women of reproductive age suffer from endometriosis, a painful and incurable disease that leaves women with severe implications for their health and overall well-being. Due to the absence of a cure and the limited effectiveness of available treatments, acquiring accurate information is paramount for women to successfully navigate both their daily lives and the complexities of the healthcare system. This scoping review aimed to map the current literature on women with endometriosis information needs, their information seeking behaviour, and the format and scope of current information resources available. Methods The scoping review was conducted using the JBI methodology for scoping reviews and reported according to the PRISMA-ScR statement. The final search was conducted in August 2024, through the databases Medline, Cinahl, Embase, Scopus, and WebofScience. Studies on information resources on endometriosis and information seeking behaviour as well as information needs of women with endometriosis were eligible for inclusion. Results The majority of the 25 included studies focused on information resources, specifically webpages and social media sites. While few studies analysed information seeking behaviour and information needs, the evidence shows women’s high interest in a broad spectrum of information topics. Across all studies, the internet was the most important access point for information. Conclusion Addressing the absence of systematic analyses on the information seeking behaviour and needs of women with endometriosis is crucial for future research. This step is essential for the development of customised information resources that cater specifically to the diverse needs of women affected by endometriosis.